2008
DOI: 10.1093/icesjms/fsn109
|View full text |Cite
|
Sign up to set email alerts
|

The optimized interpolation of fish positions and speeds in an array of fixed acoustic receivers

Abstract: Hedger, R. D., Martin, F., Dodson, J, J., Hatin, D., Caron, F., and Whoriskey, F. G. 2008. The optimized interpolation of fish positions and speeds in an array of fixed acoustic receivers. – ICES Journal of Marine Science, 65: 1248–1259. The principal method for interpolating the positions and speeds of tagged fish within an array of fixed acoustic receivers is the weighted-mean method, which uses a box-kernel estimator, one of the simplest smoothing options available. This study aimed to determine the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 19 publications
0
51
0
1
Order By: Relevance
“…1c; the configuration for 2007 was almost identical. Receivers in the continuous array were moored on a near-hexagonal grid designed to ensure complete spatial coverage, with a mean distance between neighboring receivers of 570 m. The maximum range of the transmitter within the inner bay was ~650 m, giving considerable overlap in the receiver detection ranges (Hedger et al 2008a); therefore, the configuration of receivers in the continuous array in the estuary and the inner bay was suitable for the use of non-parametric regression for the interpolation of kelt positions. Receivers outside of the continuous array (in the upper estuary and in the linear arrays in the outer bay, and in the Strait of Belle Isle) were not used for interpolating kelt positions because it was found that they provided only intermittent coverage of only some of the kelts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1c; the configuration for 2007 was almost identical. Receivers in the continuous array were moored on a near-hexagonal grid designed to ensure complete spatial coverage, with a mean distance between neighboring receivers of 570 m. The maximum range of the transmitter within the inner bay was ~650 m, giving considerable overlap in the receiver detection ranges (Hedger et al 2008a); therefore, the configuration of receivers in the continuous array in the estuary and the inner bay was suitable for the use of non-parametric regression for the interpolation of kelt positions. Receivers outside of the continuous array (in the upper estuary and in the linear arrays in the outer bay, and in the Strait of Belle Isle) were not used for interpolating kelt positions because it was found that they provided only intermittent coverage of only some of the kelts.…”
Section: Methodsmentioning
confidence: 99%
“…Then, within the continuous array (estuary and inner bay), kelt locations were interpolated using kernel smoothing; the rationale being that this could provide a fine-scale interpolation of kelt locations allowing fine-scale patterns and their causes to be identified. A normal kernel (bandwidth = 30 min) was used because this has been shown to produce less error than the box kernel (Hedger et al 2008a). For each kelt, the location was estimated at 10 min intervals (separately in easting and northing dimensions) from the coordinates of the receivers detecting the transmitter signals.…”
Section: Methodsmentioning
confidence: 99%
“…This was based on the assumption that a likely location of a transmitter whose signal was detected by several receivers and was in the middle of the receivers (cf. Hedger et al 2008). The largest of the calculated detection ranges for each transmission was considered as a minimum estimate of the detection range for that particular transmission and termed minimum detection range D min (eqn 1).…”
Section: A G E N E R a L A C O U S T I C A T T E N U A T I O N M O D mentioning
confidence: 99%
“…We used the Nadaraya-Watson normal kernel estimator (sm package in R; Bowman & Azzalini 1997) to calculate position estimates, or centre of activity (COA) locations, for monitored fish every 60 min (see Simpfendorfer et al 2002, Hedger et al 2008. Processed data were used for all of the following analyses.…”
Section: Residence Timementioning
confidence: 99%